Peran dan Kepentingan North Atlantic Treaty Organization (NATO) Dalam Konflik Perang Sipil di Libya: Studi Kasus Periode Tahun 2011-2015 - Murdani, Harisuda; Machmudi, Yon (UI Scholars Hub, 2021)
The wave of the Arab Spring in the East The Civil War in Libya that occurred in the Middle East in 2011 was felt in Libya. The conflict that started as a demonstration ended in a civil war between the government and the Libyan opposition. NATO's humanitarian intervention is the mandate of the United Nations in the civil war in Libya uses the Responsibility to Protect rule to prevent the conflict from spreading. The presence of NATO as an international community is not only due to concern for Libya but there is an interest of oil resources in Libya. During 2011-2015, NATO did not have a significant impact on the continuation of Libya after the civil war. The case problems that occurred were discussed using descriptive qualitative methods with a literature study using analysis of conflict resolution theory and the oil economy as the initial conflict trigger. The author finds that oil has the potential to make other countries involved in domestic conflicts. NATO needs to be a continuation of the oil supply in Libya. Regional and international actors determine Libya's complicated future with local factions who fighting for power.